Characterization of biased partner choice in mitotic non-allelic homologous recombination of Saccharomyces cerevisiae - Merriman, Sean, author; Argueso, Juan Lucas, advisor; Markus, Steven, committee member; Nishimura, Erin, committee member; Wiese, Claudia, committee member (Colorado State University. Libraries, 2023)
Using yeast as a model in which to study copy number variation (CNV)-generating mutations, the J.L. Argueso lab has discovered that a specific region of S. cerevisiae genome (the right arm of chromosome 7; Chr7R) is much more susceptible to sustaining deletions as a translocation recipient than other apparently similar segments of the genome. Further, Chr7R acquires amplifications as a translocation donor less frequently than other chromosomes. To begin unraveling the cause of this unusual behavior, we evaluated the effect of several candidate genes involved in chromatin mobility and sister chromatid cohesion on the mutational spectra involving Chr7R. Our results suggest that regulatory factors of chromatin mobility or sister chromatid cohesion affect the outcomes of HR-mediated repair events at Ch7R. We are hopeful that our findings will open a window into the fundamental cellular processes that are responsible for CNVs found in eukaryotic genomes, and inform translational implications for modeling this class of mutation in cancer.